(untitled) (Czech Journal of International Relations, 1995)
Václav Kural: Conflict Instead of Community? Czechs and Germans in the Czechoslovak State (1918-1938). Publishing House R in cooperation with the Institute of International Relations, Prague 1993, 272 pages, ISBN 80-901431-3-X. Václav Kural: Conflict Instead of Community! Czechs and Germans in the Greater German Reich and the Path to Expulsion (1938-1945). Institute of International Relations, Prague 1994, 296 pages, ISBN 80-85864-04-5. Jitka Vondrová (ed.): Czechs and the Sudeten German Question, 1939-1945. Documents. Institute of International Relations, Prague 1994, 347 pages + 1 map, ISBN 80-85864-05-3.